(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
The developmental and behavioral disabilities remain high in children and in adults who were born preterm. In this case assessment of quality of life and development of preterm infants can be very informative and interesting. This is a prospective longitudinal (at 3, 6, 9 and 12 months) study of preterm birth and term control infants selected from pediatric polyclinics of Yerevan. The quality of life (QL) measures were done with QUALIN questionnaire and the developmental measures with Battelle Developmental Inventory. A total of 71 preterm and 105 term control infants underwent study. Among 71 preterm birth infants, who selected on the study at 3 months, 40 infant’s score on the BDI was <–1 SD and 1 infants’ score on the BDI was <–2 SD. However, at the age of 12 months 32 of these same children showed a BDI score >85. Parents and pediatricians reported worse QL for of preterm infants compared with control group. At same time parents of preterm infants reported better QL for their children compared with pediatricians. The lowest QL and developmental scores among preterm children were detected at 3 months. Improvement of QL and developmental score was observed in the next age groups.